PENGARUH HARGA BAWANG MERAH TERHADAP PRODUKSI BAWANG MERAH DI JAWA TENGAH - Pranata, Ade; Umam, Ahmad Takhlishul (Universitas Negeri Semarang, 2015)
Onion prices are fluctuating in Central Java, causing profits onion farmers uncertain. So that when the price drops causing the farmers had a loss and decrease cultivating intensity in the next season. The data in this study using quantitative data using OLS (Ordinary Least Square) with the classical assumption: multicoloniarity, autocorrelation, heteroscedasticity, and test for normality. The test equipment are using F-test, t test, and R2. From the test results of significance (F test) showed that the independent variables simultaneously significant effect on dependent variable with the calculated F value of 7.594314 and 0.007849 probability <0.05. The results of the partial model test (t test) showed that the price of onion variables significantly influencing the production of onion variables with probability 0.0078 <Î± (0.05) and had a negative impact, with coefficient of -3,148.617. Coefficient of determination on this results is 0.117569. it could be explained that onion production is influenced by variables onion prices by 11.76% while the remaining 88.24% influenced by other variables outside the model. Recomendate : The government needs to control the price that farmers do not lose money when prices fall and can continue cultivating in the next period. So that the onion production is relatively stable.Â